Mesophase behavior of a homologous series of fluorene-ester mesogenic compounds - Gundogdu, Merve; Jeannin, Olivier; Camerel, Franck; Akdas-Kilic, Huriye; Eran, Belkiz Bilgin (ELSEVIER, 2026)
A homologous series of fluorene-based mesogens featuring ester linkages, variable terminal alkyl chains, and systematically modified aromatic cores was synthesized to probe structure-mesophase relationships. Differential scanning calorimetry and polarized optical microscopy confirmed liquid-crystalline behavior throughout the series. Molecular-level tailoring of fluorene-ester architectures enables precise control of mesophase organization: increasing alkyl chain length and extending the aromatic core drive a transition from nematic to smectic A order. The shortest-chain compound (n = 8) exhibits a nematic phase, whereas longer homologues (n = 10-14) with longer alkyl chains cores stabilize the smectic A phase. Thermal analysis shows a slight reduction in clearing temperature with chain elongation, while the Cr-SmA transition remains low and nearly invariant, reflecting the balance between core rigidity and flexible chain packing. Incorporation of a chiral citronellol terminal group induces a chiral nematic phase and a distinct blue phase, highlighting the strong coupling between molecular structure and chirality in fluorene-based liquid crystals.
Keywords: Fluorene; Ester linker; Liquid crystal; Mesophase; Calamitic; Blue phase; LIQUID-CRYSTALS; POLYMERS; ORDER; Chemistry